From Ghanaian Folk Song to Contemporary Art Music for Bb Atɛntɛbɛn and Piano - Adjahoe, Mawuyram Quessie (Malaysian Journal of Music, 2017)
In recent decades, many Ghanaian composers have incorporated traditional Ghanaian folk tunes into their western-influenced compositional works. Among them are Ephraim Amu, Joseph Hanson Kwabena Nketia, Nicholas Nichodemus Kofie, and Cosmas Worlanyo Kofi Mereku who used folk tunes as themes for extended musical compositions. These compositions represent the hybrid cultural identity of Ghanaian composers whose roots are entrenched in traditional and Western musical cultures. This article focuses on the compositional technique I, as a modern composer, utilised in integrating the musical elements and features of ‘Nyavɔ Nyee Tu Gbɔmeɖoɖoe’, a Ghanaian folk song into a new contemporary art music composition for the Bb atɛntɛbɛn (a modified traditional bamboo flute) and piano. In this new composition also titled Nyavɔ Nyee Tu Gbɔmeɖoɖoe, I extended beyond the standard tuning systems of the modified Bb atɛntɛbɛn by structuring the piece based on sonata form. The sonata form contains modulation from the tonic triggering me to include two new chromatic pitches, expanding the capabilities of the modified Bb atɛntɛbɛn. In this article, I argue for new possibilities of atɛntɛbɛn ‘neoclassical’ compositions by combining compositional techniques from western classical and Ghanaian traditional music.